2018
DOI: 10.1016/j.clinbiomech.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Increased torsional stability by a novel femoral neck locking plate. The role of plate design and pin configuration in a synthetic bone block model

Abstract: The novel plate design with its pin configuration enhanced torsional stability. To reveal clinical relevance a clinical study is planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 73 publications
4
18
0
Order By: Relevance
“…Stability testing of the same plate with three Hansson pins called the Hansson Pinloc ® system compared with two or three pins alone in a proximal femur fracture model has been performed to calculate torsional stiffness, torque at failure and failure energy. The new implant significantly improved all parameters [3]. Comparable results have been obtained with similar testing of the Dynaloc ® implant.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…Stability testing of the same plate with three Hansson pins called the Hansson Pinloc ® system compared with two or three pins alone in a proximal femur fracture model has been performed to calculate torsional stiffness, torque at failure and failure energy. The new implant significantly improved all parameters [3]. Comparable results have been obtained with similar testing of the Dynaloc ® implant.…”
Section: Introductionsupporting
confidence: 62%
“…Thus, despite the biomechanical advantage in the laboratory of Hansson pins or cannulated screws locked in a plate over pins and screws alone [3] the clinical outcomes were not so advantageous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomechanical laboratory studies with composite bone block have shown greater stiffness, torque at failure, and absorbed total energy at failure when fixed with Pinloc compared with 2 Hansson pins (Brattgjerd et al. 2018). Torsional stability is thought to be beneficial for healing of femoral neck fractures (Ragnarsson and Kärrholm 1992) and could possibly mean less pain for the patient and thus facilitate rehabilitation.…”
mentioning
confidence: 99%